2016
DOI: 10.1007/s11803-016-0330-4
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-induced collapse mechanism of two types of dangerous rock masses

Abstract: As the economy of China develops, an increasing number of key traffi c projects have been undertaken in the west of China, where there are high, steep rock slopes. The collapse of dangerous rock masses, especially following a strong earthquake, is one of common geological disasters known in rock slope engineering. Therefore, it is important to study the collapse mechanism of dangerous rock masses induced by an earthquake and the analysis approach of its stability. This study provides a simple and convenient me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Their calculation example demonstrated that the criterion could quantitatively reflect the instability of dangerous rock mass. Wang W et al (Liu et al, 2008;Wang et al, 2016) concluded that the crack extension of dangerous rock mass is closely associated with its size and initial crack length. Amitrano D (Amitrano et al, 2010) examined the stability of rock slope affected by climate change, concluding that microseismic monitoring system plays an essential function in predicting and evaluating dangerous rock hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Their calculation example demonstrated that the criterion could quantitatively reflect the instability of dangerous rock mass. Wang W et al (Liu et al, 2008;Wang et al, 2016) concluded that the crack extension of dangerous rock mass is closely associated with its size and initial crack length. Amitrano D (Amitrano et al, 2010) examined the stability of rock slope affected by climate change, concluding that microseismic monitoring system plays an essential function in predicting and evaluating dangerous rock hazards.…”
Section: Introductionmentioning
confidence: 99%
“…The collapse of dangerous rock masses is a common geological disaster in the western mountainous area of China, which threatens the environment and causes the loss of human lives and property, and also has adverse effects on engineering construction [1,2]. China is a country that experiences severe earthquake disasters, and earthquakes became a major cause of dangerous rock mass collapse in the western region [3,4]. Therefore, it is of great significance to study the dynamic stability analysis methods of dangerous rock masses under seismic action.…”
Section: Introductionmentioning
confidence: 99%